Simulation and analysis drag and lift coefficient between sedan and hatchback car - Mohd Khalil Azingah, Salleh (2009)
This thesis presents research about the difference coefficients barriers and lift coefficients for two basic design types of sedan and hatchback cars. The objective of this thesis is to identify drag and lift coefficient.. Process simulation and analysis for both the model design was conducted with computer-aided drawing software and analyzed using software COSMOSFloworks. From the results of coefficients can be concluded that barriers and lift coefficients for both types of design is different. Restriction coefficient and lift coefficient for the hatchback design is much lower than the sedan design. This means that the hatchback design is more efficient and aerodynamics value is higher. This assessment and differences between the two designs is very meaningful for determining the design of more efficient designs in the car now. Results also able to enhance the security features on the car at once can reduce fuel consumption used. Results are also able to improve the design of the car in early development in the future.